Decolorization of liquid sugar products by carbon sorbents - Gusyatinska, Natalia; Hryhorenko, Nataliia (My University, 2025)
The aim of this work is to scientifically substantiate the use of carbon sorbents in adsorption purification (decolorization) of liquid sugar products, as well as to identify the patterns of this process. The study utilized a sugar-containing product derived from sweet sorghum. To intensify the purification process and remove coloring agents from the liquid sugar product, carbon sorbents were employed: CS grade (produced by modifying regenerated wood-based raw materials), NORIT GAS 1240, and coconut-based carbon C607. Метою цієї роботи є наукове обґрунтування використання вуглецевих сорбентів для адсорбційного очищення (знебарвлення) рідких цукрових продуктів, а також виявлення закономірностей цього процесу. У дослідженні використовувався цукровмісний продукт, отриманий із цукрового сорго. Для інтенсифікації процесу очищення та видалення барвників з рідкого цукрового продукту були використані вуглецеві сорбенти: марки CS (отриманий шляхом модифікації регенерованої деревної сировини), NORIT GAS 1240 та вуглець C607 на основі кокосу.
Keywords: кафедра технології цукру і підготовки води; sugar syrup; carbon sorbent; decolorization of solutions; цукровий сироп; вуглецевий сорбент; знебарвлення розчинів